Aplikasi Android Penyedia Informasi Alat Transportasi Umum (Studi Kasus : Angkutan Umum Di Terminal Kampung Rambutan) - Parno Parno; Febriani Febriani; Andhika Prakasa Kasma (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
The advancing technology and increasing number of android users make people want theirinformation available anytime, anywhere, and easily used especially to search information. Just like thisapplication that made for Terminal Kampung Rambutan. This application is made to help users, especiallymass transport users, by providing them with information about mass transport. By this application, userscan save time and energy. Application made with java language programming and design with eclipse IDEand android SDK. Research method that used to build this application is planning, designing and testing.This application can help users to find mass transport information quickly and correctly.Key Word : Aplication, Information, Kampung Rambutan, Android